Associação entre obesidade e adipocinas na saliva e fluido gengival crevicular: uma revisão sistemática e meta-análise - Leticia Fernanda Duffles Rodrigues (2018)
Association between obesity and adipokines´ levels in saliva and gingival crevicular fluid: a systematic review. Obesity is an increasing disease characterized by accumulation of fat in different organs and tissues. Currently, adipose tissue has been described as an endocrine organ, once it secrets a lot of metabolic active molecules, inflammatory cytokines and adipokines. Several molecules are classified as adipokines and they are classically evaluated in blood or adipose tissue. Recent studies have been evaluating adipokines in gingival crevicular fluid (GCF) and saliva and its relation to obesity. The objective of this systematic review was to evaluate the association between obesity and the concentration of adipokines in gingival crevicular fluid (GCF) and saliva. The search was conducted in four databases. Manual and Google Scholar searches were also conducted. Two calibrated authors performed study selection, data extraction and quality assessment of included articles. Thirty four articles were included. Metaanalysis demonstrated that TNF- concentration in saliva was statistically increased in individuals with obesity compared with individuals without obesity. In contrast, concentrations of resistin, adiponectin, leptin, ghrelin and IL-6 in saliva and of resistin, adiponectin, leptin, IL-6, IL-8, TNF-, IL-8 and PAI-1 in GCF, were statistically similar in individuals with and without obesity. Overall, the scientific evidence regarding altered levels of specific adipokines in saliva and or GCF among persons with obesity is weak, except for salivary TNF-. The limited availability and heterogeneity of data do not allow us to state whether changes of adipokines in GCF and saliva are associated with obesity or otherwise.